The Frontal Sinus Surgical Approaches and Controversies. - Georgalas, Christos (Thieme Medical Publishers, Incorporated, 2022)
""This book will be a valuable resource for novice surgeons approaching one of the most challenging anatomical subsites, since it provides a stepwise approach to understanding the anatomical background, the radiological aspects, and the broad spectrum of different surgical approaches to the frontal sinuses.The authors are to be congratulated for this masterpiece, which will become the gold standard for experts and beginners."" --Paolo Castelnuovo Edited by renowned rhinologists and skull base surgeons Christos Georgalas and Anshul Sama, this complete guide to frontal sinus surgery covers surgi.